Comportement alimentaire de quelques espèces d’Holothuries aspidochirotes inféodées aux herbiers de Posidonie de la côte de Mostaganem (Stidia) - HAOUAS, Sid Ali; OULD MOUSSA, Hicham (My University, 2016)
The aspidochirote sea cucumbers are echinoderms very characteristic by their feeding behavior « deposit – feeders ».This is the major representative of the benthic compartment of the ecosystem Posidonia Oceanica. A study of feeding behavior of aspidochirotide [Holothuria (H.) tubulosa,Holothuria (L.) poli, Holothuria (P.) forskali and Holothuria (P.) sanctori] subservient to the Posidonia seagrass was conducted at Stidia (Mostaganem) at an average depth of -3m . Our study focuses on the analysis of the organic matter of the sediment of the three sections of the digestive tract of these species, the substrate of their habitats, and their faeces, in order to have insights into their selective ability overlooked matter organic. The assimilation efficiency was also discussed. Sea cucumbers aspidochirote studied show a little selective behavior for organic matter. This selectivity is exercised only by H. sanctori and H. forskali and shows strong values in May (spring period) for the two species, which coincides with the period of their reproductions. The high values of assimilation efficiency for organic matter in the studied species are observed in spring season, which also coincides with their reproduction periods. These are the species Holothuria tubulosa and Holothuria forskali assimilates best organic matter.
Keywords: Holothuries aspidochirotes; sélectivité; matière organique; comportement alimentaire; assimilation; Mostaganem.; Sea cucumbers; aspidochirote; selectivity; organic matter; feeding behavior